Effect of Chinese herbal medicine therapy on risks of all-cause mortality, infections, parasites, and circulatory-related mortality in HIV/AIDS patients with neurological diseases - Chiou, Jian-Shiun; Chou, Chen-Hsing; Ho, Mao-Wang; Tien, Ni; Liang, Wen-Miin; Chiu, Mu-Lin; Tsai, Fuu-Jen; Wu, Yang-Chang; Chou, I-Ching; Lu, Hsing-Fang; Lin, Ting-Hsu; Liao, Chiu-Chu; et al. (Frontiers in Pharmacology, 2023)
Long-term living with human immunodeficiency virus (HIV) and/or antiretroviral therapy (ART) is associated with various adverse effects, including neurocognitive impairment. Heterogeneous neurocognitive impairment remains an important issue, affecting between 15–65% of human immunodeficiency virus infection and acquired immunodeficiency syndrome (HIV/AIDS) patients and resulting in work performance, safety, and health-related outcomes that have a heavy economic burden. We investigated the effect of Chinese herbal medicine (CHM) on the risk of all-cause mortality, infections, parasites, and circulatory-related mortality in HIV/AIDS patients with neurological diseases in Taiwan. We identified 1,209 HIV/AIDS patients with neurological diseases during 2010– 2017. The Kaplan–Meier method, log-rank test, and Cox proportional hazards model were used to analyze 308 CHM users and 901 non-CHM users within this population. Major CHM clusters were determined using association rule mining and network analysis. Results showed that CHM users had a 70% lower risk of all-cause mortality (adjusted hazard ratio (aHR) = 0.30, 95% confidence interval (CI):0.16-0.58, p < 0.001) (p = 0.0007, log-rank test). Furthermore, CHM users had an 86% lower risk of infections, parasites, and circulatory-related mortality (aHR = 0.14, 95% confidence interval (CI):0.04-0.46, p = 0.001) (p = 0.0010, log-rank test). Association rule mining and network analysis showed that two CHM clusters were important for patients with neurological diseases. In the first CHM cluster, Huang Qin (HQ; root of Scutellaria baicalensis Georgi), Gan Cao (GC; root of Glycyrrhiza uralensis Fisch.), Huang Lian (HL; root of Coptis chinensis Franch.), Jie Geng (JG; root of Platycodon grandiflorus (Jacq.) A.DC.), and Huang Bai (HB; bark of Phellodendron amurense Rupr.) were identified as important CHMs. Among them, the strongest connection strength was identified between the HL and HQ. In the second CHM cluster, Suan-Zao-Ren-Tang (SZRT) and Ye Jiao Teng (YJT; stem of Polygonum multiflorum Thunb.) were identified as important CHMs with the strongest connection strength. CHMs may thus be effective in treating HIV/AIDS patients with neurological diseases, and future clinical trials are essential for the prevention of neurological dysfunction in the population.